2001
DOI: 10.1038/sj.cr.7290067
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of γ-aminobutyric acid transporter subtype I leads to susceptibility to kainic acid-induced seizure in transgenic mice

Abstract: γ-aminobutyric acid (GABA) is the principal inhibitory neurotransmitter, and the GABAergic synaptic transmission is normally terminated by the rapid uptake through GABA transporters. With transgenic mice ubiquitously overexpressing GABA transporter subtype I (GAT1), the present study explored the pathophysiological role of GAT1 in epileptogenesis. Though displaying no spontaneous seizure activity, these mice exhibit altered electroencephalographic patterns and increased susceptibility to seizure induced by kai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Although still somewhat controversial, many studies have shown that the expression of AMPA-, KA-and NMDA-sensitive receptors as well as the GABA A receptor is either constant or variably diminished in many different brain regions including the hippocampus during aging (Gonzales et al, 1991;Pittaluga et al, 1993;Le Jeune et al, 1996;Nicolle et al, 1996;EcklesSmith et al, 2000;Kuehl-Kovarik et al, 2000;Magnusson, 2000;Sonntag et al, 2000;Wenk and Barnes, 2000;Adams et al, 2001;Clayton and Browning, 2001;Clayton et al, 2002;Lerma et al, 2001). Differences in a variety of other factors, including voltage-gated calcium channels (Vigues et al, 1999;Kelly et al, 2003), androgen levels (Mejias-Aponte et al, 2002;Ramsden et al, 2003;Ciriza et al, 2004), and GABA receptor function (MacGregor et al, 1997;Ma et al, 2001) which have been shown to modulate kainate-induced seizure activity in young animals, may modulate susceptibility in aged animals as well.…”
Section: Discussionmentioning
confidence: 99%
“…Although still somewhat controversial, many studies have shown that the expression of AMPA-, KA-and NMDA-sensitive receptors as well as the GABA A receptor is either constant or variably diminished in many different brain regions including the hippocampus during aging (Gonzales et al, 1991;Pittaluga et al, 1993;Le Jeune et al, 1996;Nicolle et al, 1996;EcklesSmith et al, 2000;Kuehl-Kovarik et al, 2000;Magnusson, 2000;Sonntag et al, 2000;Wenk and Barnes, 2000;Adams et al, 2001;Clayton and Browning, 2001;Clayton et al, 2002;Lerma et al, 2001). Differences in a variety of other factors, including voltage-gated calcium channels (Vigues et al, 1999;Kelly et al, 2003), androgen levels (Mejias-Aponte et al, 2002;Ramsden et al, 2003;Ciriza et al, 2004), and GABA receptor function (MacGregor et al, 1997;Ma et al, 2001) which have been shown to modulate kainate-induced seizure activity in young animals, may modulate susceptibility in aged animals as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that homozygous GAT1 2/2 mice exhibited impaired hippocampusdependent learning and memory [18]. We also found that overexpression of GAT1 led to cognitive deterioration in transgenic mice [19]. Interestingly, the heterozygous and homozygous GAT1 knockout mice showed opposite behavioral response to some of the actions of ethanol, including locomotor stimulation, preference, and reward [17].…”
mentioning
confidence: 99%
“…Neurotransmitter transporters play an important role in controlling of neural signal transmission, dysfunction in expression of neurotransmitter transporter genes may cause different diseases [7][8][9]. To determine if there is NET expressed in cardiac sympathetic system, RT-PCR was carried out from total RNA of rat myocardium and cardiac sympathetic ganglia.…”
Section: Resultsmentioning
confidence: 99%